EFFECTS OF ENSILING FORAGE TURNIP (BRASSICA RAPA) PLANT HARVESTED IN DIFFERENT VEGETATION PERIODS WITH TRITICALE (X TRITICOSECALE WITTMACK) FORAGE AT DIFFERENT RATIOS ON SILAGE QUALITY, IN VITRO DIGESTIBILITY AND ENERGY CONTENT - Serhat YILDIZ; Suphi DENIZ; Fatma ÖZKAN; Çagri KALE (Journal of Animal and Plant Sciences, 2023)
This study determined silage quality, in vitro digestibility and energy contents in forage turnip (Brassica rapa L.) harvested in three different vegetation periods, and it was used without (control) or with 10, 20, 30, 40% triticale (X Triticosecale Wittmack). As the vegetation period progressed, the dry matter (DM), organic matter (OM), neutral detergent fiber (NDF) and acid detergent fiber (ADF) contents increased, and the crude ash (CA), crude protein (CP) and ether extract (EE) contents decreased (p<0.05). The effects of the triticale ratio on the parameters between the groups were significant (p<0.05) except for ADF. As this ratio increased, the DM, CA and NDF contents of the silages increased, their OM levels decreased, and there was no change in CP, EE and ADF. As the vegetation period progressed, the lactic acid (LA) and acetic acid (AA) contents of the silages decreased, and their Fleig scores increased (p<0.05). The effects of triticale ratio on the parameters were significant except for propionic acid (PA) (p<0.05). As the vegetation period progressed, the dry matter digestibility (DMD), organic matter digestibility (OMD) and energy values of the silages decreased (p<0.05). In comparison to the control, the highest DMD, OMD and energy levels were found with triticale added at 20%. If forage turnip is ensiled with triticale forage at ratios of 10% to 30%, the obtained silages are quality silages, and can be used as an alternative, quality source of roughage in the ruminants feeding.
Keywords: Digestibility; Energy content; Forage turnip; Silage; Triticale